ANALISIS KELAYAKAN PENULISAN BERITA PADA PORTAL BERITA ISLAM ONLINE PANCARAN.NET - Nurman Ando Setianas Nugroho (Institut Islam Mamba'ul 'Ulum Surakarta, 2021)
This research analyzed the news quality on an Islamic online news portal in Solo, thepancaran.net, and the concern about the quality of Islamic online media in Solo became the reason for this research. This is a descriptive research using qualitative approach., andthe research data analysis used descriptive analysis. The process was carried out since the data were collected;therefore, researchers had started the data analysis process on the field until the research was complete. The analysis usedparameters, whether the news hadfulfilled the elements of news,and thus the news could be said to be in good quality, less quality, or not worthy of publication due to the code of ethics violation. These elements were news value, 5W + 1H systematic, Inverted Pyramid Systematics, News Headlines, News Lead, News Content, News Quotations, and Journalistic Code of Ethics. In the analysis, there were 7 elements fulfilled in the news onpancaran.net, therefore if there was one element that had not been fulfilled, then the news on pancaran.net could be said to be in good quality, sinceit would have been good if these 7 elements had been fulfilled. However, there was one element that was not fulfilled, which was the element of the journalistic code of ethics. It was found on this research that the pancaran.netwebsite was not recommended for online news readers in Solo due to violations of the journalistic code of ethics found in the news.